The epidermal growth factor family has a dual role in deciding the fate of cancer cells - Memon, A A ; 0000-0002-1081-3553; Sorensen, Sandahl B; Nexo, E (Scandinavian Journal of Clinical and Laboratory Investigation, 2006)
Expression of the epidermal growth factor (EGF) receptors HER1 and HER2 has been implicated in tumour growth and poor survival, whereas expression of HER3 and HER4 has been associated with improved survival of bladder cancer patients. The balance between the expression of the EGF family members may therefore have a role to play in determining the final outcome in cancer cells. To check this, we examined the effect of HER1 activation and inhibition on the expression of the EGF receptors HER3 and HER4 and ligands - the heregulins (HRGs). RT4 bladder cancer cells were treated with 1nM HB-EGF (known to induce cell proliferation by activating HER1 receptor) and the mRNA content of the two receptors (HER3 and HER4) and their activating ligands (HRG1-HRG4) was quantified by real time PCR at indicated time-points. Expressions of HRG1alpha and HRG1beta increased 8-fold and 9-fold, respectively, whereas the expressions of HRG2alpha (4-fold), HRG2beta (2.5-fold) and HRG4 (3.5-fold) decreased. In contrast, inhibition of tyrosine kinase activity of HER1 with 5 microM Iressa (a specific inhibitor of HER1) resulted in an increase in mRNA expression of HRG2alpha (2.5-fold) and HRG4 (1.5-fold). In addition, expression of the receptors HER3 (1.5-fold) and HER4 (2-fold) was also increased. In conclusion, we demonstrate that activation of the HER1 receptor suppressed the expression of a specific set of HRGs. A decrease in expression of HRG2 and HRG4 during HB-EGF treatment supports their role in growth inhibition, whereas an increase in HRG1 expression points to a role as a growth stimulatory member of the EGF family.
Keywords: Biomarkers/metabolism; Cell Differentiation; Cell Line, Tumor; Epidermal Growth Factor/genetics; ErbB Receptors/antagonists & inhibitors; Gefitinib; Gene Expression Regulation, Neoplastic; Humans; Ligands; Multigene Family; Quinazolines/pharmacology; RNA, Messenger/metabolism; Receptor, ErbB-2/genetics; Receptor, ErbB-3/genetics; Receptor, ErbB-4; Urinary Bladder Neoplasms/metabolism